Nomenclature and typifications in Celmisia (Asteraceae: Astereae): The New Zealand endemic subgenera Caespitosae, Glandulosae, and Lignosae - Saldivia, Patricio (Phytotaxa, 2023)
As part of ongoing taxonomic studies on the subtribe Celmisiinae, a nomenclatural analysis of names validly published in Celmisia subgenera Caespitosae, Glandulosae and Lignosae is presented, including 10 new lectotypifications.